The Relevance of the Philosophy of Science in the Digital Era: Epistemological Challenges and the Integrity of the Scientific Method - Ilham Akbar Maulana; Khairul Anas; Efendi; Muhammad Zalnur (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The digital era has fundamentally transformed the ways in which knowledge is produced and legitimized. The emergence of artificial intelligence (AI), the proliferation of big data, and the dominance of algorithmic systems have not only accelerated scientific research but have also posed significant challenges to the philosophical foundations of science. This article aims to explore the relevance of the philosophy of science amid digital disruption by examining two major issues: the epistemological challenges to the status of scientific truth and the crisis of integrity in the scientific method. Using a conceptual-philosophical analysis, the study investigates the black box phenomenon in AI, which obscures scientific transparency, as well as the realities of the post-truth era and algorithm-driven echo chambers that shift the authority of truth from academic consensus to algorithmic amplification. Furthermore, the article highlights contemporary challenges to the integrity of the scientific method, including the difficulty of replicating studies based on dynamic datasets and the increasing prevalence of instant scientific fabrication. Drawing on Karl Popper's epistemology of falsification and Thomas Kuhn's theory of paradigm shifts, the study concludes that the philosophy of science should not remain a passive observer. In the digital age, it serves as an ethical and methodological compass as well as a critical safeguard for reforming the standards of validity, objectivity, and the demarcation of scientific knowledge to ensure the credibility and sustainability of science in the future.